A Retrospective Study of Endoscopic Findings in Patients Presenting with Dyspepsia in a Rural Teaching Hospital - Gurung, Dhiraj; Khati, S. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Dyspepsia is a common problem faced in our country and elsewhere. Benign causes predominate with occasional incidences of carcinoma of the stomach, esophagus. The presence of warning signs helps indicate the presence of such carcinomas though various studies differ as to its usefulness. Methods: Patients presenting with dyspepsia were investigated with a gastroscope to see the etiological pattern seen in the Karnali region and the usefulness of the warning signs. This study included the initial 100 patients undergoing upper gastrointestinal endoscopy for dyspepsia evaluation in our institution. Results: The majority of the patients (53%) showed normal findings on visual examination despite being symptomatic suggestive of functional dyspepsia. The most common warning sign was weight loss which had a positive predictive value of only 4%. Malena was present in 10% of the patients with a positive predictive value of 30%. Conclusions: Significant weight loss as a warning sign to screen patients for gastrointestinal pathology seems unsuitable in the rural setting.